PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DI PT. PEGADAIAN (PERSERO) - Darma Satria; Azhadi Halomoan; Rizaldy Syahputra; Vadly Syafril (Cross-border, 2020)
Globalization has had a strong influence on Human Resource Management (HRM) and has created a complexity of problems. These challenges must be faced by making a paradigm shift and improving management in each organization, by placing Human Resources (HR) as a priority. The lack of regulations that bind employees is also an obstacle so that disciplinary issues cannot be applied clearly. All of these things are increasingly having an impact on less than optimal performance to the company. The approach used in this research is the quantitative method. Test data quality using validity and reliability tests. The research location was conducted at PT. Pegadaian (Persero) Medan Regional Office. The object of this research is leadership style as variable X and employee performance as variable Y. Variables of leadership style, work motivation and individual competence show a very real influence on employee performance at PT. Pegadaian (Persero) Medan with a value of Fcount> Ftable (18,681> 2.73) and a significant value of 0.000. Leadership style has a positive and significant effect on employee performance at PT. Pegadaian (Persero) Medan with tcount> ttable (3.547> 1.993) and a significant value of 0.001.